2012
DOI: 10.2486/indhealth.ms1314
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Contaminant Distribution in the Breathing Zone

Abstract: Conventionally, the "breathing zone" is defined as the zone within a 0.3 m (or 10 inches) radius of a worker's nose and mouth, and it has been generally assumed that a contaminant in the breathing zone is homogeneous and its concentration is equivalent to the concentration inhaled by the worker. However, several studies have mentioned that the concentration is not uniform in the breathing zone when a worker is close to the contaminant source. In order to examine the spatial variability of contaminant concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The 2010 census revealed that the migrant worker population is 230 million. 10 Population migration plays a critical role in the spread of infectious diseases and affects the emergence, re-emergence and changes in the prevalence of infectious diseases. 23 , 24 The migrant population often faces greater difficulties in accessing appropriate health care for diagnosis and treatment because of a lack of knowledge about disease, which is a result of low education and poor economic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2010 census revealed that the migrant worker population is 230 million. 10 Population migration plays a critical role in the spread of infectious diseases and affects the emergence, re-emergence and changes in the prevalence of infectious diseases. 23 , 24 The migrant population often faces greater difficulties in accessing appropriate health care for diagnosis and treatment because of a lack of knowledge about disease, which is a result of low education and poor economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The employed population reached 780 million, including a rapidly growing population of 226 million migrant workers, who migrate predominantly from the rural central and western regions to the large coastal cities. 10 Migrant workers frequently have lower education levels and less access to health care. Consequently, the weighted up-to-date and age-appropriate immunisation rates for childhood vaccines, such as the diphtheria, tetanus and pertussis combined vaccine, the oral poliomyelitis vaccine, the hepatitis B vaccine and the measles-containing vaccine, were significantly lower in the children of migrant workers than in those of the non-migrant population in the Beijing area.…”
Section: Introductionmentioning
confidence: 99%
“…temperature of the walls and room, and natural convection due to heat flux from the bodies. Turbulence has been observed to be an important phenomenon for accuracy of CFD modelling and for the optimum location of sampling points [ 14 , 22 , 24 , 31 33 ]. The temperature of the room and EMONO were included in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Fluent CFD software (ANSYS, PA, USA) was used to compute the N 2 O concentration in each part of the room (millions of points), at every second of the administration process, for each scenario. Because the location of the measurement point is known to influence the TWA-8 h value [ 22 , 33 , 34 ], a virtual sensor (probe) was positioned by the HCP’s mouth, to be representative of the inhaled exposure. The N 2 O exposure level for the HCP (TWA-8 h ppm) was computed using the simulated values of N 2 O concentration at this probe throughout the simulated scenario.…”
Section: Methodsmentioning
confidence: 99%
“…Occupational diseases not only affect workers' health by adding a significant disease burden, but also decrease the productivity and profitability of commercial enterprises, as well as social harmony and stability 1 , 2) . For example, at the 1st International Occupational Health Forum & 3rd China-US Occupational Health Symposium, held at the Beijing International Center in Beijing, China, from August 22 to August 23, 2017, about five hundred occupational health researchers and practitioners from China, the US and other countries agreed that occupational diseases have become an important factor in restricting the sustainable development of the social economy.…”
Section: Introductionmentioning
confidence: 99%